Peran Pemuda Karang Taruna Bunga Bakung Dalam Pembangunan Di Desa Metun Sajau Kecamatan Tanjung Palas Timur Kabupaten Bulungan Kalimantan Utara - Merang, K. Rapiandi Isak; Robert, Robert (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2019)
The aim of the study was to determine the youth role of the Karang Bakuna Youth in the development of Metun Sajau Village and to find out the obstacles faced by the young people of the Karang Bakuna Bunga Bakung in the development of Metun Sajau Village. Type of qualitative descriptive research. The informants were the Karang Taruna management, members of the Bunga Bakung Youth Organization, the Village Secretary, the Indigenous Village administrators of Metun Sajau Village, and the People of the Metun Sajau Village Community. Data collection techniques are observation, interviews, and documentation. Data analysis techniques are data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that the role of the youth of the Bunga Bakung Youth Organization in the development of Metun Sajau Village can be seen from the physical development including construction of road facilities, construction of traditional houses, construction of field stands, and construction of sports facilities. Roles in non-physical development include expressing opinions in village meetings, maintaining security and order, and preserving regional arts. The constraints faced by the Flower Village Youth Organization in the development in Metun Sajau Village are limited funding, lack of facilities and infrastructure, lack of communication and coordination from the leadership, busy due to work, less assertive leadership of the Karang Taruna organization, lack of awareness of the village's role and function Taruna, and the lack of attention of the village government